Bioactive compounds in mothers milk affecting offspring outcomes: A narrative review. Issue 7 (20th January 2022) - Gregg, Brigid; Ellsworth, Lindsay; Pavela, Gregory; Shah, Kruti; Berger, Paige K.; Isganaitis, Elvira; VanOmen, Sheri; Demerath, Ellen W.; Fields, David A.
Summary: Background: Compared to the exhaustive study of transgenerational programming of obesity and diabetes through exposures in the prenatal period, postnatal programming mechanisms are understudied, including the potential role of breast milk composition linking maternal metabolic status (body mass index and diabetes) and offspring growth, metabolic health and future disease risk. Methods: This narrative review will principally focus on four emergent bioactive compounds [microRNA's (miRNA), lipokines/signalling lipids, small molecules/metabolites and fructose] that, until recently were not known to exist in breast milk. The objective of this narrative review is to integrate evidence across multiple fields of study that demonstrate the importance of these compositional elements of breast milk during lactation and the subsequent effect of breast milk components on the health of the infant. Results: Current knowledge on the presence of miRNA's, lipokines/signalling lipids, small molecules/metabolites and fructose in breast milk and their associations with infant outcomes is compelling, but far from resolved. Two themes emerge: (1) maternal metabolic phenotypes are associated with these bioactives and (2) though existing in milk at low concentrations, they are also associated with offspring growth and body composition. Conclusion: Breast milk research is gaining momentum though we must remain focused on understanding how non‐nutritive bioactive components are affected by the maternal phenotype, how they subsequently impact infant outcomes. Though early, there is evidence to suggest fructose is associated with fat mass in the 1st months of life whereas 12, 13 diHOME (brown fat activator) and betaine are negatively associated with early adiposity and growth.